A tool to promote sustainability in casting processes: Development highlights - Pagone, Emanuele; Jolly, Mark R.; Salonitis, Konstantinos (Springer, 2017)
The validity of traditional manufacturing decision variables (i.e. cost, quality, flexibility and time) is questioned by some important challenges of our time: the scarcity of natural resources and environmental pollution. Increasing energy cost to extract and process natural resources, alongside regulatory pressures against pollution, pushes very mature and competitive processes like casting towards a holistic approach where sustainability contributes to strategic decisions together with the mentioned traditional manufacturing variables. As a contribution to this industrial necessity, a modular tool able to analyse material and energy flows in casting processes is under development. In particular, the ability to represent automatically Sankey diagrams of the flows recently implemented is described and validated.
Keywords: Sustainable manufacturing systems; Energy efficiency; Casting